Nitrogen fertilization promoted microbial growth and N2O emissions by increasing the abundance of nirS and nosZ denitrifiers in semiarid maize field - Fudjoe, Setor Kwami; Li, Lingling; Anwar, Sumera; Shi, Shangli; Xie, Junhong; Wang, Linlin; Xie, Lihua; Yongjie, Zhou (Frontiers in Microbiology, 2023)
Nitrous oxide (N2O) emissions are a major source of gaseous nitrogen loss, causing environmental pollution. The low organic content in the Loess Plateau region, coupled with the high fertilizer demand of maize, further exacerbates these N losses. N fertilizers play a primary role in N2O emissions by influencing soil denitrifying bacteria, however, the underlying microbial mechanisms that contribute to N2O emissions have not been fully explored. Therefore, the research aimed to gain insights into the intricate relationships between N fertilization, soil denitrification, N2O emissions, potential denitrification activity (PDA), and maize nitrogen use efficiency (NUE) in semi-arid regions. Four nitrogen (N) fertilizer rates, namely N0, N1, N2, and N3 (representing 0, 100, 200 and 300 kg ha−1 yr−1, respectively) were applied to maize field. The cumulative N2O emissions were 32 and 33% higher under N2 and 37 and 39% higher under N3 in the 2020 and 2021, respectively, than the N0 treatment. N fertilization rates impacted the abundance, composition, and network of soil denitrifying communities (nirS and nosZ) in the bulk and rhizosphere soil. Additionally, within the nirS community, the genera Cupriavidus and Rhodanobacter were associated with N2O emissions. Conversely, in the nosZ denitrifier, the genera Azospirillum, Mesorhizobium and Microvirga in the bulk and rhizosphere soil reduced N2O emissions. Further analysis using both random forest and structural equation model (SEM) revealed that specific soil properties (pH, NO3--N, SOC, SWC, and DON), and the presence of nirS-harboring denitrification, were positively associated with PDA activities, respectively, and exhibited a significant association to N2O emissions and PDA activities but expressed a negative effect on maize NUE. However, nosZ-harboring denitrification showed an opposite trend, suggesting different effects on these variables. Our findings suggest that N fertilization promoted microbial growth and N2O emissions by increasing the abundance of nirS and nosZ denitrifiers and altering the composition of their communities. This study provides new insights into the relationships among soil microbiome, maize productivity, NUE, and soil N2O emissions in semi-arid regions.